Intestinal obstruction with a twist: a rare case of congenital portal vein aneurysm causing intestinal obstruction. (21st September 2018) - Chandran, Shanu; Kumar, Manish; Jacob, Tarun John K; Mohamed, Ferzine
Abstract : Bilious vomiting is often a presenting feature of upper intestinal obstruction in newborn. We present a case of intestinal obstruction in a newborn baby caused by abnormal vascular band arising from portal vein aneurysm in association with a midgut volvulus. Congenital anomalies of portovenous system are very rare, and it usually presents with portal hypertension in late infancy or childhood. In this particular child, the portal vein aneurysm contributed to intestinal obstruction due to both a failure of intestinal rotation and a mechanical band over the transverse colon.